Fermented Aronia melanocarpa pomace improves the nutritive value of eggs, enhances ovarian function, and reshapes microbiota abundance in aged laying hens - Li, Zhihua; Qin, Binghua; Chen, Ting; Kong, Xiangfeng; Zhu, Qian; Azad, Md. Abul Kalam; Cui, Yadong; Lan, Wei; He, Qinghua (Frontiers in Microbiology, 2024)
There is a decline in the quality and nutritive value of eggs in aged laying hens. The performance, egg nutritive value, lipid metabolism, ovarian health, and cecal microbiota abundance were evaluated in aged laying hens (320 laying hens, 345day-old) fed on a basal diet (control), and basal diet inclusion of 0.25%, 0.5%, and 1.0% fermented Aronia melanocarpa pomace (FAMP) for eight weeks, respectively. The results show that 0.5% FAMP reduced the saturated fatty acids (such as C16:0) and improved the healthy lipid indices in egg yolks by decreasing the atherogenicity index, thrombogenic index, and hypocholesterolemia/hypercholesterolemia ratio and increasing health promotion index and desirable fatty acids (P < 0.05). Additionally, FAMP supplementation (0.25%-1.0%) increased (P < 0.05) the ovarian follicle-stimulating hormone, luteinizing hormone, and estrogen 2 levels, while 1.0% FAMP upregulated the HSD3B1 expression. The expression of VTG II and ApoVLDL II in the 0.25% and 0.5% FAMP groups, APOB in the 0.5% FAMP group, and ESR2 in the 1% FAMP group were upregulated (P < 0.05) in the liver. The ovarian total antioxidant capacity was increased (P < 0.05) by the 0.25%-1.0% FAMP supplementation. Dietary 0.5% and 1.0% FAMP downregulated (P < 0.05) the Keap1 expression, while 1.0% FAMP upregulated (P < 0.05) the Nrf2 expression in the ovary. Furthermore, 1.0% FAMP increased cecal acetate, butyrate, and valerate contents and Firmicutes while decreasing Proteobacteria (P < 0.05). Overall, FAMP improved the nutritive value of eggs in aged laying hens by improving the liver-blood-ovary function and cecal microbial and metabolite composition, which might influence economic benefits.